Routledge International Handbook of Critical Policing Studies - Asquith, Nicole L. (London and New York: Routledge, Taylor & Francis, 2025)
"This handbook identifies the key issues facing the police and safety governance across the globe and offers insights into the implications for policing theory and practice, proposing solutions to some of the most intransigent problems facing contemporary societies. Individually, and as a collection, this handbook will be an essential read for scholars, practitioners, and activists alike"
Keywords: Police; Law enforcement